Stabilität und Wandel von Arbeitsmarktinstitutionen aus wettbewerbsökonomischer Sicht - Anna Göddeke; Justus Haucap; Annika Herr; Christian Wey (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2011)
– This contribution gives an overview of the main results of our theoretical research on the stability and change of labour market institutions. We use so-called models of unionised oligopolies which are borrowed from the theory of industrial organization in order to analyse the effects of simultaneous market power in both labour and product markets. The focus of our research is on the interaction between various organisational structures of labour markets and different forms of product market competition. In particular, we analyse some recent developments in Germany, such as the introduction of sector-specific minimum wages, the formation of craft unions, the increasing number of profit sharing contracts as well as the relocation of production facilities to foreign countries.
Keywords: 330; Arbeitsmarktpolitik; institutionelle Faktoren; politischer Wandel; Tarifvertrag; Tarifbindung; Wettbewerbstheorie; Arbeitsmarkttheorie; Mindestlohnrecht; Tarifrecht; Oligopol; Absatzmarkt; Arbeitsmarkt; Flächentarifvertrag; Gewinnbeteiligung; Arbeitsbeziehungen; internationaler Wettbewerb; outsourcing; Ausland; Niedriglohnland; Post; Mindestlohn